Performance enhancement of amorphous WO3 assisted graphene-based electronic devices: Aspect of surface engineering - Kim, Seung Il; Hyeong, Seok Ki; Park, Dong Seop; Hyun, Sang Hwa; Moon, Ji Yun; Lee, Sangyeob; Kim, Tae Sung; Lee, Seoung Ki; Lee, Jae Hyun; Heo, Keun (Applied Surface Science, 2021)
After the successful synthesis of graphene using chemical vapor deposition in 2009, the large-area/defect-free transfer method still remains a critical issue for implementing high-performance graphene-based electronic devices. Here, for the first time, we demonstrated a specially prepared water-soluble amorphous WO3 intermediate layer to effectively protect the graphene surface from immediately after its synthesis to transfer and final unit processing. Moreover, using the photodetector to which the proposed protection method was applied, the performance improvement was quantitatively verified. Compared with the control device, the surface-protected photodetector recorded a higher photoresponsivity of 1.74 times and faster temporal photoswitching response time of 4 s or more. The graphene surface protection method using the WO3 intermediate layer allows the reversibility in transfer process and performance enhancement of graphene-based electronic devices.
Keywords: CVD grapheme; Dry transfers; Electronics devices; Intermediate layers; Performance; Performance enhancements; Photodetector; Protection methods; Surface protection; WO3 intermediate layer; CVD grapheme; Dry transfer; Photodetector; Surface protection; WO3 intermediate layer